Combining yield potential and drought resilience in a spring wheat diversity panel. (18th September 2020) - Griffiths, Cara A.; Reynolds, Matthew P.; Paul, Matthew J.
Abstract: Pressures of population growth and climate change require the development of resilient higher yielding crops, particularly to drought. A spring wheat diversity panel was developed to combine high‐yield potential with resilience. To assess performance under drought, which in many environments is intermittent and dependent on plant development, 150 lines were grown with drought imposed for 10 days either at jointing or at anthesis stages in Obregon, Mexico. Both drought treatments strongly reduced grain numbers compared with the fully irrigated check. Best performers under drought at jointing had more grain than poor performers, while best performers under drought at anthesis had larger grain than poor performers. Most high‐yielding lines were high yielding in one drought environment only. However, some of the best‐performing lines displayed yield potential and resilience across two environments (28 lines), particularly for yield under well‐watered and drought at jointing, where yield was most related to grain numbers. Strikingly, only three lines were high yielding across all three environments, and interestingly, these lines had high grain numbers. Among parameters measured in leaves and grain, leaf relative water content did not correlate with yield, and proline was negatively correlated with yield; there were small but significant relationships between leaf sugars and yield. This study provides a valuable resource for further crosses and for elucidating genes and mechanisms that may contribute to grain number and grain filling conservation to combine yield potential and drought resilience. Abstract : Pressures of population growth and climate change require the development of resilient higher yielding crops, particularly to drought. To assess performance under drought, which in many environments is intermittent and dependent on plant development, 150 lines were grown with drought imposed for 10 days either at jointing or at anthesis stages in Obregon, Mexico. Several high‐yield lines across all drought trials were identified.